Pendaftaran Jaminan Fidusia sebagai Syarat Eksekusi yang Sah: Analisis Hukum Positif Indonesia - Michael Charlie Tanuwijaya (Journal of Legal, Political, and Humanistic Inquiry, 2026)
The ambiguity in the legal construction regarding the status of fiduciary registration as a prerequisite for the validity of execution within Indonesia’s positive legal system has become increasingly complex following decisions of the Mahkamah Konstitusi, which restrict parate execution and emphasize the necessity of procedural justice. The inconsistency between Law Number 42 of 1999 and its practical implementation particularly executions conducted without registration or lawful mechanisms has generated legal uncertainty and potential violations of the rights of debtors and third parties. This study employs a normative legal method with statutory, conceptual, and case approaches through an analysis of legislation, legal doctrines, and relevant judicial decisions. Legal materials are collected through library research and analyzed using systematic, grammatical, and teleological interpretation. The findings reveal that fiduciary registration is constitutive in nature, serving as the basis for the creation of proprietary rights and the legitimacy of execution. The validity of execution cannot rely solely on the existence of a fiduciary certificate but must also comply with procedural requirements as interpreted by the Constitutional Court.